Training and Counselling of Sex Education as a Prevention for Sexual Risk Behaviour in Adolescents: A Quasi-experiment Study - Saragih, Hanna Sriyanti; Gultom, Lusiana (Universitas Airlangga, 2025)
Adolescents have a high sense of curiosity, including issues of sexuality. Adolescents' curiosity about sexuality is due to the developmental period of adolescents entering puberty, which is marked by the maturation of the reproductive system and the production of sex hormones. Risky sexual behaviour is sexual behaviour that can cause negative impacts such as unwanted pregnancy, abortion and sexually transmitted diseases. Adolescents need to be equipped with various knowledge about reproductive health, which includes understanding the physiology of reproductive organs, menstruation, fertility, sexual orientation, STI/HIV/AIDS prevention techniques, pregnancy, family planning techniques and skills. Objectives: To determine the effect of sex education through training and counselling as a preventive measure against risky sexual behaviour in adolescents: Participants of the Adolescent Reproductive Health Information and Counselling Center (PIK-KRR) in Medan City. Method: This research uses a quasiexperimental group pre-test and post-test design. The number of samples in this study was 30 adolescents. The statistical test analysis method used the paired sample t-test with the SPSS application. Results: This research shows an increase in adolescents' knowledge, attitudes and actions regarding risky sexual behaviour (p-value <0.05). Conclusion: Health services provide education about reproductive health knowledge and the impact of dangers of engaging in sexual behaviour to all adolescents so that they gain useful knowledge so as not to do other negative things.